Preventive interventions for paternal perinatal depression: a scoping review protocol. Issue 3 (8th March 2023) - Iwata, Hiroko; Mori, Emi; Maehara, Kunie; Kimura, Kayoko; Toyama, Fusae; Kakehashi, Asana; Seki, Marika; Abe, Sayaka; Kosaka, Mai
Abstract : Introduction: The objective of this scoping review is to map the literature describing preventive interventions for paternal perinatal depression. Depression is a common mental disorder experienced by fathers as well as mothers around childbirth. Perinatal depression has negative consequences for men, and suicide is the most serious adverse effect. Impaired father–child relationships can also result from perinatal depression, negatively impacting child health and development. Considering its severe effects, early prevention of perinatal depression is important. However, little is known about preventive interventions for paternal perinatal depression including Asian populations. Methods and analysis: This scoping review will consider studies of preventive interventions for perinatal depression in men with a pregnant wife or partner, and new fathers (less than 1 year post partum). Preventive intervention includes any form of intervention intended to prevent perinatal depression. Primary prevention intended to promote mental health will also be included if depression is included as an outcome. Interventions for those with a formal diagnosis of depression will be excluded. MEDLINE (EBSCOhost), CINAHL (EBSCOhost), APA PsycINFO (EBSCOhost), Cochrane Central Register of Controlled Trials and Ichushi-Web (Japan's medical literature database) will be searched for published studies, and Google Scholar and ProQuest Health and Medical Collection will be searched for grey literature. Beginning in 2012, the search will include the last 10 years of research. Screening and data extraction will be performed by two independent reviewers. Data will be extracted using a standardised data extraction tool and presented in diagrammatic or tabular form, accompanied by a narrative summary. Ethics and dissemination: As this study involves no human participants, approval from a human research ethics committee is not required. Findings of the scoping review will be disseminated through conference presentations and publication in a peer-reviewed journal. Trial registration number: https://osf.io/fk2qe/ .